Conductivity of 1-Ethyl-3-Methylimidazolium Chloride (EMIC) and Aluminum Chloride (AlCl3) Ionic Liquids at Different Temperatures and AlCl3 Mole Fractions. (8th September 2020) - Shinde, Pravin; Ahmed, Aninda N.; Nahian, Md K.; Peng, Yuxiang; Reddy, Ramana G.
Abstract : The conductivity (k) of ionic liquid (IL) comprising a melt of 1-ethyl-3-methylimidazolium chloride (EMIC) and aluminum chloride (AlCl3 ) with different AlCl3 mole fractions (XAl ) and temperatures (343-383 K) are reported. XAl values of 0.6, 0.643, and 0.667 in EMIC-AlCl3 IL are selected to maintain the desired Lewis acidity. Precise and fast conductivity measurements and the behavior of anion species in IL are studied using electrochemical impedance spectroscopy (EIS). The measured k data followed the Arrhenius law using which the activation energies ( E a ) of conduction are determined. The conductivity of EMIC-AlCl3 IL decreased with the higher XAl . EMIC-AlCl3 with XAl =0.6 exhibited higher k (5.58 S m –1 ) at 383 K and lowest E a (4.25 KJ mol –1 ) among studied parameters. Based on the thermodynamic calculations, the differences in conductivities are attributed to the interplay of anion concentration, the molecular structure, cation-anion interactions, and hydrogen bonds in the IL.